For Whom the Mind Wanders, and When - Kane, Michael J.; Brown, Leslie H.; McVay, Jennifer C.; Silvia, Paul J.; Myin-Germeys, Inez; Kwapil, Thomas R. (Psychological Science, 2007)
An experience-sampling study of 124 undergraduates, pretested on complex memory-span tasks, examined the relation between working memory capacity (WMC) and the experience of mind wandering in daily life. Over 7 days, personal digital assistants signaled subjects eight times daily to report immediately whether their thoughts had wandered from their current activity, and to describe their psychological and physical context. WMC moderated the relation between mind wandering and activities' cognitive demand. During challenging activities requiring concentration and effort, higher-WMC subjects maintained on-task thoughts better, and mind-wandered less, than did lower-WMC subjects. The results were therefore consistent with theories of WMC emphasizing the role of executive attention and control processes in determining individual differences and their cognitive consequences.